Citizen´s organizations in the knowledge and information society: new media, new forms of participation - Cabello Cádiz, Patricio (Revista Colombiana de Ciencias Sociales, 2014)
Our relationship with the media and with the sources that inform the public opinion is changing. Its transformation has occurred in line with the transformation in the forms and dynamics of social organization, with the emergence of new socio-technical hybrids serving politics, and with the productive and creating praxis resulting from collective action. Traditional media, concentrated on easily identifiable socioeconomic groups, give way to new forms of communication that emerge as citizens’ initiatives rather than as products. This is not a simple amplification of individual archetypes, but an activation of forms of collective organization that seem to fill the void left by the crisis of representation of institutional politics, which is observed in countries with authoritarian regimes as in developed countries living in democracy. We can argue that this change of focus of media communication is undoubtedly one of the most significant changes in recent years.